Calcifying Pseudoneoplasm of the Neuraxis Involving the Posterior Skull Base: A Case Report and Literature Review. (October 2021) - Yan, Lei; Dileep Menon, Preethi; Heim-Hall, Josefine; Hackman, Sarah
Calcifying pseudoneoplasm of the neuraxis is an uncommon, nonneoplastic fibro-osseous lesion of the central nervous system. At the time of this report, at least 150 cases have been reported in the literature. Because of the rarity of this lesion, it is often diagnostically challenging for radiologists and pathologists alike. In this article, we present a case of a 44-year-old woman with a 5.8-cm intracranial/skull base calcifying pseudoneoplasm of the neuraxis that was concerning for osteosarcoma on initial frozen section. Permanent sections revealed bone and fibrous stroma, calcifications, and nests of histiocytes with granuloma formation. Scattered, focally dense inflammatory foci and spindled cells outlining abundant large nodules of chondromyxoid matrix were also present. In this case report, we also reviewed recent literature for clinical presentations, radiologic findings, and histologic differential diagnoses. Familiarity with this lesion is important to avoid misdiagnosis leading to unnecessary and potentially harmful treatment.